Analysis technologies firewall - Корнієнко, Б.Я. (Proceedings of National Aviation University, 2006)
With the purpose of research of properties and maintenance of protection of the information in telecommunication systems and information systems is lead the comparative analysis of technologies of firewalls. Three basictechnologies of firewalls are considered: on the basis of popular free-of-charge sources of program maintenance, commercial program decisions and hardware-software decisions. Results of researches are presented in tables and conclusions.